2015
DOI: 10.14238/pi55.5.2015.287-92
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the quality of life in cerebral palsy children with physical therapy more and less than 10 months

Abstract: Background Cerebral palsy (CP) is the most common cause of severe physical disability in childhood. These limitations may cause lower level experience or quality of life (QoL). Physical therapy (PT) plays a central role in managing CP. ConclusionsCerebral palsy children who received more than 10 months PT have higher QoL than children with less than 10 months PT. There was significant gross motor improvement after PT in both groups. [Paediatr Indones. 2015;55:287-92].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
0
8
2
2
Order By: Relevance
“…The 16 included studies (Table ) reported on HRQoL of children and/or adolescents with CP and totaled 1579 participants (i.e. children and adolescents with CP; not inclusive of controls).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 16 included studies (Table ) reported on HRQoL of children and/or adolescents with CP and totaled 1579 participants (i.e. children and adolescents with CP; not inclusive of controls).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in eight countries: Turkey ( n =7), India ( n =2), Thailand ( n =2), Brazil ( n =1), China ( n =1), Indonesia ( n =1), Iran ( n =1), and Malaysia ( n =1) . Of the studies, there were two cross‐sectional, two case‐control, one prospective descriptive study, and four validation studies . The remaining studies did not specify, however they met criteria for cross‐sectional ( n =5) and case‐control ( n =2) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations